Preparation, Characterization and Antibacterial Activity of NiO Nanoparticles - Santhoshkumar, A.; Kavitha, Helen P.; Suresh, R. (Asian Journal of Chemistry, 2016)
In present investigation, the synthesis of nickel oxide (NiO) nanoparticles is performed using thermal decomposition method. The As-prepared NiO nanoparticles was characterized by X-ray diffraction analysis, Fourier transform infrared spectroscopy, scanning electron microscopy and energy dispersion X-ray spectroscopy. Antibacterial activity of NiO nanoparticles was tested against Bacillus subtills, Streptococcus pneumonia, Escherichia coli and Proteus vulgaris. The results show that the synthesized NiO nanoparticles will be great potential in the field of nanomedicine.